Knowledge of newborn care practices among caregivers attending immunization clinic at a tertiary care centre of Lucknow: a cross-sectional study - Singh, Sujata; Yadav, Kriti; Choudhary, Ranjana (International Journal Of Community Medicine And Public Health, 2019)
Background: Essential newborn care (ENC) provides for an opportunity to assess the infant’s growth and development and counsel mothers regarding proper newborn care. Acquainting the caregivers with knowledge pertaining to dangers signs, hygienic practices, feeding, weaning, health and nutrition including growth and behaviour of children, might affect the rearing of their children. Therefore the present study aims to study the knowledge of caregivers in relation to newborn care. Methods: A descriptive cross sectional study was conducted among the caregivers attending the immunization clinic in a tertiary care centre (King George's Medical University) in Lucknow between January- March, 2016. A pretested and structured interview questionnaire was used to collect data and analysis was done using SPSS ver 16.0. Results: In Majority (75%) of the caregivers the knowledge regarding ENC was found to be average. Only 4% of the caregivers had good knowledge of ENC. Among the variables the association of knowledge of ENC and age of the caregiver< 30 years, general caste, level of education of the caregiver of high School and above, middle socioeconomic status, female sex of the newborn, birth order of 2 or more, >4 ANC visits and new born care not discussed in the VHND being conducted in the area were found to be statistically significantly. Conclusions: On the whole, the results of our study indicated that most of the caregivers were having unsatisfactory knowledge of child care practices. The present scenario can be improved through enhancing information education and counselling activities, training of health workers and mothers focusing on newborn health care practices.